The restless heart [large type] - Hoag, Tami (Thorndike Press large print famous authors, 2009)
Globe-trotting photographer Danielle doesn't think she'll survive six weeks in New Orleans, babysitting her sister's five children. Then help arrives in the from of tall, dark, Cajun Remy Doucet.